Menguji Faktor–Faktor Determinasi Belanja Produk Fashion Apparel Saat Live Streaming Di Media Sosial - Rachmat Prasetya, Febriansyah; Suhud, Usep; Aditya, Shandy (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to analyze the influence of social influence, customer trust, shopping lifestyle, fashion involvement and impulsive buying intention variables on live streaming purchase decisions through social media in Jabodetabek. The data collection method uses a survey method with purposive sampling on a Likert scale. The object of this study were 200 respondents who were buying fashion apparel by impulse, live buying at online stores while live streaming via social media. This study used SPSS software version 24 and SEM (Structural Equation Modeling) AMOS version 24 for data analysis. The results showed: (1) social influence has a positive and significant effect on impulsive buying intention, (2) customer trust has a positive and significant effect on impulsive buying intention, (3) shopping lifestyle has a positive and significant effect on impulsive buying intention. (4) fashion involvement has a positive and significant effect on impulsive buying intention. (5) impulsive buying intention has a positive and significant effect on live streaming purchase decisions.